The Implementation of the Contextual Teaching Learning (CTL) Model to Increase Student Interest and Metacognition at SMP Negeri 2 Batukliang - Sofiyan Hidayat; Fathurrahman Muhtar (CV. Creative Tugu Pena, 2024)
This study aims to determine the results of the application of the Contextual Teaching Learning (CTL) learning model in improving the interest and metacognition of students at SMPN 2 Batukliang. The subjects of this study were 28 students of Class VIII C of SMPN 2 Batukliang. Data collection techniques used questionnaires, interviews, notes and documentation. The method used in this study was a qualitative descriptive method, and simple statistics were used to calculate the questionnaire data. From the PTK activities using the CTL learning model that had been carried out with 3 cycles, namely cycle I, cycle II and cycle III, the interest and metacognition of students at SMPN 2 Batukliang experienced a significant increase. Therefore, it can be concluded that the CTL model has succeeded in increasing the interest and metacognition of students at SMPN 2 Batukliang.